2020
DOI: 10.3390/ani10040686
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Time-Fed Concentrate-Based Diets on Plasma Metabolites, Rumen Histology, and mRNA Expression of Hepatic Enzymes of Wethers

Abstract: Transition to grain increases inflammation and causes parakeratosis, which can decrease growth performance in fattening animals. It is unknown if ruminants adapt to these inflammatory responses over time. In a three-phase, 49-day experiment, all wethers (n = 13, BW = 50.6 ± 4.7 kg; 4.9 ± 0.3 months of age) were fed an 80% forage diet during P1(day 0 to 21). On day 21, 4 wethers were slaughtered to obtain baseline liver and rumen tissue. During P2 (day 22 to 25), the remaining wethers were fed an 80% concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 39 publications
(62 reference statements)
1
3
0
Order By: Relevance
“…Albumins represent 40–60% of total proteins in circulation and the decreased albumin concentrations is a consequence of reduced synthesis which may be due to increased utilization of amino acids for the synthesis of cytokines and APPs (Girardi et al, 2018 ; Tothova et al, 2014 ). In accordance with our findings, feeding HC diet downregulated ALB gene expression in sheep (Chishti et al, 2020 ). Supranutritional Se supplementation attenuated the expressions of HC diet‐induced APPs in liver.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Albumins represent 40–60% of total proteins in circulation and the decreased albumin concentrations is a consequence of reduced synthesis which may be due to increased utilization of amino acids for the synthesis of cytokines and APPs (Girardi et al, 2018 ; Tothova et al, 2014 ). In accordance with our findings, feeding HC diet downregulated ALB gene expression in sheep (Chishti et al, 2020 ). Supranutritional Se supplementation attenuated the expressions of HC diet‐induced APPs in liver.…”
Section: Discussionsupporting
confidence: 93%
“…HC diet‐derived LPS elicits acute phase response (APR) by regulating the synthesis and secretion of acute phase proteins (APPs) in liver thus any fluctuation in their concentrations in the peripheral blood reflects the functional disturbance and inflammation of liver (Guo et al, 2017 ; He et al, 2019 ; Minuti et al, 2015 ). Many studies have reported that HC diets increased levels of positive APPs and decreased negative APPs in peripheral blood of ruminants (Chandra et al, 2018 ; Ohtaki et al, 2020 ; Zhang et al, 2016 ) accompanied with alteration at transcriptional level in liver (Chishti et al, 2020 ; Li et al, 2019 ). Moreover, the modulation of hepatic APPs genes expressions in LPS‐challenged goats, sheep, and cattle (Cao et al, 2006 ; Jiang et al, 2008 ; Wang et al, 2017 ) indicate that HC diet induce hepatic inflammatory response through LPS translocated from GIT via portal vein (Chang, Zhang, Xu, Jin, Guo, et al, 2015 ; Chang, Zhang, Xu, Jin, Seyfert, et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations